2022
DOI: 10.3389/fpubh.2022.880506
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Dietary Fiber and Vitamin C Intake and Oral Cancer

Abstract: BackgroundDietary fiber and vitamin C has been reported to play a possible role in tumorigenesis. However, few studies have estimated their association with oral cancer risk. In this project, we investigated the relationship between dietary fiber and vitamin C and oral cancer risk in adults in Southern China.Methods382 patients newly diagnosed with oral cancer were matched to 382 hospital derived controls by frequency matching in age and sex. Pre-diagnostic consumption of dietary fiber and vitamin C intake wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…Following a similar trajectory, a case–control examination conducted in southeastern China, with 382 oral cancer patients and 382 matched controls, revealed a significant association between dietary fiber, vitamin C intake, and oral cancer risk. Individuals with higher intakes of dietary fiber and vitamin C had substantially lower odds of developing oral cancer, with a 53% and 40% reduction in risk, respectively ( Table 1 ) [ 62 ]. Healthcare providers may consider the integration of biomarker testing into OSCC screening and monitoring protocols.…”
Section: Oxidative Stress and Antioxidant Mechanism In Oral Cancer Re...mentioning
confidence: 99%
“…Following a similar trajectory, a case–control examination conducted in southeastern China, with 382 oral cancer patients and 382 matched controls, revealed a significant association between dietary fiber, vitamin C intake, and oral cancer risk. Individuals with higher intakes of dietary fiber and vitamin C had substantially lower odds of developing oral cancer, with a 53% and 40% reduction in risk, respectively ( Table 1 ) [ 62 ]. Healthcare providers may consider the integration of biomarker testing into OSCC screening and monitoring protocols.…”
Section: Oxidative Stress and Antioxidant Mechanism In Oral Cancer Re...mentioning
confidence: 99%
“…139 Interestingly, numerous studies have also demonstrated that human dietary intake of DF reduces the incidence of several other cancers, including oral, prostate, liver, and breast. [140][141][142][143] Many studies suggest that the gut microbiota may act as transmitters of DF-inhibiting cancer signals. Mushroom polysaccharides (MP) may fulfill colon cancer preventive and therapeutic functions by dynamically regulating host immune responses.…”
Section: Cancermentioning
confidence: 99%
“…139 Interestingly, numerous studies have also demonstrated that human dietary intake of DF reduces the incidence of several other cancers, including oral, prostate, liver, and breast. 140–143…”
Section: Dietary Fiber Regulation Of Host Metabolism and Diseasesmentioning
confidence: 99%
“…Posa ve C vitamini alımının, ağız kanseri hastalarında (8,15 g/gün) kontrol grubuna (8,88 g/gün) göre önemli ölçüde daha düşük olduğu sonucuna varılmıştır. 14 Uzun süre yetersiz diyet posası alımının, inflamasyon için önemli bir risk faktörü olduğu bilinmektedir. Yetersiz posa alımı, sağlıklı bağırsak mikrobiyotasının gelişimini engellemesi sonucunda bütirat dâhil olmak üzere KZYA'ların üretimini azaltmaktadır.…”
Section: Di̇yet Posasinin Sağlik üZeri̇ndeki̇ Etki̇leri̇unclassified